Polyhydroxybutrate filled clamshell biofiller: effect of polyvinylpyrrolidone - Othman, Maizatulnisa; Hashim, Mohd Yusoff; Ibrahim, Nor Azowa; Khalid, Khalissani; Al-Bat'hi, Souad A. M. (Trans Tech Publications, 2015)
A totally green biocomposite was prepared via melt blending technique by using polyhydroxybutyrate (PHB) as a matrix, clamshells powder (CaCO3) as a reinforcing filler and polyvinylpyrrolidone (PVP) as a binder. PHB/CaCO3 was fixed at 70:30 ratio and PVP weight content varied at 3, 5, 7 and 9 wt%. The properties of the biocomposite have been studied in term of mechanical properties and morphology. The results showed that incorporation of PVP increased the tensile modulus which remarkably demonstrated by the enhancement in stiffness of the biopolymer. While, elongation at break decreased in an opposite behavior. Surface morphology observation on the tensile fracture samples shows the presence of microvoids, due to binding effect of the PVP.